Alkaloid Enantiomers from Isatis tinctoria with Neuroprotective Effects against H2O2-Induced SH-SY5Y Cell Injury - Xi, Yu-Fei; Lou, Li-Li; Xu, Zhi-Yong; Hou, Zi-Lin; Wang, Xiao-Bo; Huang, Xiao-Xiao; Song, Shao-Jiang (Planta Medica, 2019)
Six pairs of alkaloid enantiomers including 11 new alkaloids (1a/1b–5a/5b, 6a) were isolated from the leaves of Isatis tinctoria. Their structures were established by extensive spectroscopic analyses. Enantiomers were separated successfully by chiral chromatographic column and the absolute configurations of all isolates were determined by comparison of experimental and calculated electronic circular dichroism spectra. The isolated alkaloids were evaluated for their neuroprotective activities against H2O2-induced cell injury in human neuroblastoma SH-SY5Y cells. The results showed that 5a/5b and 6a/6b exhibited potent neuroprotective activities at 50 µM compared with the H2O2-treated group.
Keywords: Isatis tinctoria; Brassicaceae; alkaloids; enantiomers; neuroprotective effects